Emotional Regulation and Resilience in Students with Disabilities - Devi, Jessica Sekar Adhika; Huwae, Arthur (Universitas Muhammadiyah Metro, 2023)
Education is a fundamental right for every citizen of Indonesia. However, in reality, disabled students are frequently subjected to discriminatory attitudes, frequently viewed as troublesome and pitiable individuals. The impact experienced by disabled students is that they are more likely to be easily disheartened, lack confidence, and easy experience stress. Low emotional regulation causes disabled students to be unable to control their emotions and affects their resilience. Consequently, this study aimed to determine the relationship between emotion regulation and resilience in disabled students. The research employed a quantitative method with a correlational design to determine the relationship between emotion regulation and resilience. The study's participants comprised 86 disabled students aged 18 and 27 who studied at Satya Wacana Christian University, Malang State University, and Gadjah Mada University. The sampling technique utilised snowball sampling. The Emotion Regulation Questionnaire (α=0,851) and The Connor-Davidson Resilience Scale (α=0,914) were used for the study's measurement. The findings revealed a positive relationship between emotion regulation and resilience (r=0,207, sig. = 0,028). Emotion regulation affects resilience by 4%. High emotional regulation could enhance resilience in disabled students.